FULLERENE C60 AS A REGULATOR OF PHYSIOLOGICAL AND BIOCHEMICAL PARAMETERS OF WHEAT AND PEAS - Prylutska, Svitlana; Tkachenko, Tetiana (European Science, 2025)
It was studied the effect of colloidal water-soluble nanostructured fullerene C60 on morphometric, physiological and biochemical parameters of peas and wheat under different growing conditions, including the influence of drought. It was found that nanopar